Comprehensive pan-cancer analysis and experimental validation reveal FCHSD1 as a potential biomarker for diagnosis, immune infiltration, and prognosis - Liu, Ming; Ding, Guixin; Tang, Gonglin; Liu, Shangjing; Mao, Qiancheng; Wang, Xidong; Zou, Qingsong; Wu, Jitao (Frontiers in Oncology, 2025)
BackgroundFCHSD1 is a member of the F-BAR family containing one amino terminal F-BAR domain and two SH3 domains. At present, there are no relevant pan-cancer comprehensive studies on the predictive potential and immune infiltration of FCHSD1 for cancer.MethodsFCHSD1 expression profiles were analyzed through the use of various tools, including TIMER, GEPIA, R packages, and the UALCAN database. The genetic alteration status of FCHSD1 in human pan-cancer was studied using the cBioPortal website. The effect of FCHSD1 on immune infiltration was examined using the TIMER and TISIDB databases. We confirmed the association between FCHSD1 expression and patient prognosis using survival analysis from GEPIA and R packages. The drug database was utilized to analyze the sensitivity of FCHSD1 to drugs. The FCHSD1 interactive genes were obtained through the STRING and GeneMANIA platforms, respectively, and analyzed by GO and KEGG. The expression and function of FCHSD1 in renal cancer cells and tissues have also been biologically validated in vitro.ResultsFCHSD1 expression was found to be elevated in tumor tissues compared to adjacent tissues. The expression of FCHSD1 varied across different clinical stages, pathological stages, immune types, and molecular subtypes. Higher expression of FCHSD1 predicts worse outcomes for several cancer types, such as CHOL and KIRC. High FCHSD1 expression was positively correlated with immune cell infiltration in different cancer types. Additionally, the FCHSD1 co-expression gene network may be involved in endocytosis. In vitro experiments revealed that the expression of FCHSD1 in renal cancer cells and tissues was higher than that in normal cells and adjacent non-cancerous tissues. Functional assays revealed that FCHSD1 knockdown significantly suppressed proliferation and migration in ACHN and 769P cells.ConclusionFCHSD1 has the potential to serve as a prognostic and immunological marker for pan-cancer, and may also be a crucial target for future immunotherapy.